2002
DOI: 10.1677/joe.0.1750307
|View full text |Cite
|
Sign up to set email alerts
|

High stromal and epithelial human gh gene expression is associated with proliferative disorders of the mammary gland

Abstract: We have demonstrated and localized human GH (hGH) gene expression in surgical specimens of normal human mammary gland and in proliferative disorders of the mammary gland of increasing severity using sensitive in situ RT-PCR methodology. hGH mRNA identical to pituitary hGH mRNA was first detected by RT-PCR of RNA derived from samples of normal human mammary gland. Cellular localization of hGH gene expression in the normal mammary gland exhibited restriction to luminal epithelial and myoepithelial cells of the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
1
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 81 publications
(48 citation statements)
references
References 44 publications
1
45
1
1
Order By: Relevance
“…Patients with breast cancer exhibit increased serum concentrations of GH (42) and IGF-I (43), and autocrine production of human GH increases cell numbers in mammary carcinoma as a consequence of both increased mitogenesis and decreased apoptosis (44,45). Increased expression of GH with respect to normal mammary gland has been associated with proliferative disorders, including invasive ductal carcinoma (46). In the case of PRL, it has been reported that as many as 44% of patients with metastatic breast disease have been hyperprolactinaemic at some stage during the course of the disease (47), and the presence of bioactive PRL in human breast cancer cells acts in an autocrine manner to stimulate cell proliferation (48).…”
Section: Discussionmentioning
confidence: 99%
“…Patients with breast cancer exhibit increased serum concentrations of GH (42) and IGF-I (43), and autocrine production of human GH increases cell numbers in mammary carcinoma as a consequence of both increased mitogenesis and decreased apoptosis (44,45). Increased expression of GH with respect to normal mammary gland has been associated with proliferative disorders, including invasive ductal carcinoma (46). In the case of PRL, it has been reported that as many as 44% of patients with metastatic breast disease have been hyperprolactinaemic at some stage during the course of the disease (47), and the presence of bioactive PRL in human breast cancer cells acts in an autocrine manner to stimulate cell proliferation (48).…”
Section: Discussionmentioning
confidence: 99%
“…A particular and essential role for neoplasia progression of autocrine production of Prl has been revealed [34,38] . Only autocrine, but not exocrine GH, is suggested to promote neoplasia [39][40][41] .…”
Section: Jak-stat Signaling and Carcinogenesismentioning
confidence: 99%
“…GH overexpression is associated with proliferative diseases in animals and humans (Raccurt et al, 2002). Acromegalic patients have an increased risk for developing cancer (Webb et al, 2002;Jenkins, 2004;Siegel and Tomer, 2005).…”
Section: Downstream Signalling Of Ghmentioning
confidence: 99%